Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The role of international non-governmental organizations in non-international armed conflictsLawyer / Raad Muhammad Hassan Al-Badri2. Measuring the desire of the Employees of the Ministry of Hajj and Umrah in Saudi Arabia  to implement KaizenMrs. Nesreen Abdul-Raheem Siddiq, Dr. Zenah Mahmoud Al-Kubaisy3. Fifth-generation wars and their impact on international peace and security: "The Russian-Ukrainian war as a model"Dr. Badr Abdellah Bourouihiya4. The effectiveness of social media sites in achieving customer satisfaction in The Kingdom of Saudi Arabia, 2023Dr. Tareg Mohamed Elmahei Elbashier5. The impact of transformational leadership on the effectiveness of decision-making: An Applied Study on General HospitalMr. Yousef Dwaihi Al-Barakani6. Identifying the reality of training at King Khalid University and its effects on improving performance through job satisfaction among employeesAsst-Prof. Mohamed Ahmed Alsadig, Lecturer \ Abdallah Mushabab Omran7. Roles of e-Management Systems in School Administration to keep pace with Vision 2030  of KSA in Makkah (2022)Mrs. Badriah Mohammad Muner Alotaibi
Keywords: Journal of Economic, Administrative and Legal Sciences